Kangean Island Marketplace Design and Development Using Hybrid Model - Sulistyowati; Rachman, Andy; Kurniawan, Muchammad; Anam, Choirul; Eka Putra, Ricky; Salim, Ach. Khafid; Fakhrur Rozi, Nanang (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2022)
The use of the web as a promotional medium or as a media to help sales of a product is no longer a difficult thing. Currently the web is needed by anyone, from government offices, hospitals, schools, even to MSMEs in Indonesia. Marketplace is one form of application that can be used by users as a place for buying and selling community products or MSMEs. Kangean Marketplace is a place for buying and selling community products in Kangean, Madura, East Java, Indonesia. Palau Kangean is one of the islands in Sumenep Regency, Madura, East Java. Kangean Island itself is a small island that can be reached by boat transportation where the journey takes between 10 to 15 hours from Sumenep. Marketplace needs are needed by the Kangean community. The development of Kangean Marketplace utilizes the checklist method, Merapi Analysis Framework, and the Incremental Model. From the test results, it was found that the Kangean marketplace web application received an assessment of 80,08%, which means that the Kangean marketplace is suitable for use by the Kangean community